Combined lifestyle, mental health, and mortality in US cancer survivors: a national cohort study - Liu, Zhao-yan; Wang, Chen; Zhang, Yao-jun; Zhu, Hui-lian (Journal of translational medicine, 2022)
Background Adopting healthy lifestyles and staying mentally health are two cost-effective modifiable strategies that cancer survivors can implement in self-management. We aimed to evaluate the independent, mediation, interaction, and joint associations of combined lifestyle and mental health with mortality in cancer survivors. Methods We performed a cohort study including 3145 cancer survivors from National Health and Nutrition Examination Survey (2005-2018). A healthy lifestyle score was constructed based on post-diagnosis body mass index, physical activity, diet, smoking, and drinking. Post-diagnosis mental health was assessed by Patient Health Questionnaire (PHQ-9). Hazard ratios (HRs) and 95% confidence intervals (CIs) for all-cause, cancer, and non-cancer mortality were computed using Cox proportional hazards regression models. Results After 20,900 person-years of follow-up (median, 6.3 years), cancer survivors with higher lifestyle score had decreased mortality, independent of mental health. Compared to participants with lower lifestyle score (0-1), HRs (95% CIs) for all-cause and non-cancer mortality among those with higher lifestyle score (3-5) were 0.68 (0.52-0.89) and 0.69 (0.56-0.85), respectively. 6.2-10.3% of the associations were mediated by mental health. Similar trends were observed among participants categorized by mental health, those with better mental health had lower mortality, independent of lifestyle. Participants with better mental health benefited more from adopting healthy lifestyles, and vice versa. Combinations of higher healthy lifestyle score and better mental health were associated with significant decreased mortality, the lowest mortality was seen in participants with highest healthy lifestyle score and concurrently with best mental health. Conclusions For the first time, in this cohort study with a nationally representative sample of US cancer survivors, we comprehensively explored the complex associations of lifestyle, mental health, and mortality. Evidence derived from this study may give much confidence to cancer survivors and healthcare providers that, changing one's lifestyle and/or staying mentally healthy after cancer diagnosis can improve survival. Keywords: Lifestyle, Mental health, Mortality, Cancer survivor